PERAN ORANG TUA TERHADAP KETERAMPILAN MENYIKAT GIGI DAN MULUT PADA ANAK DISABILITAS INTELEKTUAL - Leny Pratiwi Arie Sandy (Universitas Gadjah Mada, 2017)
Intellectual disability is a group of children with impaired intellectual function below an average of 70 or lower. This group experienced problems in terms of self-development skills such as tooth brushing. Tooth brushing is an activity the mechanical removal of from food scraps, germs and plaque. Growing and developing independence of children with intellectual disability was influenced by the role of parents. Parents who have a role as basic of children behavior was contributed to process child growth. This study aims to determine the relationship of parental role to the tooth brushing skill in intellectual disability children.This research method is analytic survey and used cross sectional design. Sampling technique using total sampling. The population in this research is intellectual disability children in SLB Pamardi Putra Banguntapan Bantul Yogyakarta as many as 30 people. The role of parent was measured using questionnaire and tooth brushing skills measured using check list (from Special Care Advocates in Dentistry (SAID) guidelines, 1995). Data analysis using Spearman correlation with significance level (0,05). The result of this research is p = 0.185 (> 0.05), it shows that there is no significant correlation between parent role to oral and brushing skills in intellectual disability children in SLB Pamardi Putra Banguntapan Yogyakarta.